A new interrelatedness indicator to measure economic complexity, with an application to the Portuguese Case - Lopes, João Carlos (2009)
This paper is about economic complexity, treated as interrelatedness between the parts or sectors of an economy, particularly one represented by an input-output system. The complexity indicator proposed capture two relevant features of interrelatedness that can be separately measured: a dependency effect and a network effect. This indicator can be used in two contexts: the direct connections given by the technical coefficient matrix, A and the total (direct plus indirect and induced) effects given by the Leontief inverse, (I-A)-1. The first results of an empirical application to the Portuguese Case are presented, covering the period 1980-1999.